2019
DOI: 10.1038/s41467-019-09146-5
|View full text |Cite
|
Sign up to set email alerts
|

Rho-dependent transcription termination in bacteria recycles RNA polymerases stalled at DNA lesions

Abstract: In bacteria, transcription-coupled repair of DNA lesions initiates after the Mfd protein removes RNA polymerases (RNAPs) stalled at the lesions. The bacterial RNA helicase, Rho, is a transcription termination protein that dislodges the elongation complexes. Here, we show that Rho dislodges the stalled RNAPs at DNA lesions. Strains defective in both Rho and Mfd are susceptible to DNA-damaging agents and are inefficient in repairing or propagating UV-damaged DNA. In vitro transcription assays show that Rho disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Over the last decade, it has been established that the Rho-dependent termination has a genome-wide effect ( 20 , 21 , 22 ), which directly or indirectly enabled Rho to function as a regulator of many physiological processes ( 4 ). Our laboratory has recently shown that Rho augments DNA repair ( 6 ) and controls bacterial antibiotic sensitivity via multipartite pathways ( 7 ). Likely, its RNA binding, as well as RNA translocase activities, could also impart its roles in various RNA metabolism processes, RNA chaperone activities, and RNA turnover functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, it has been established that the Rho-dependent termination has a genome-wide effect ( 20 , 21 , 22 ), which directly or indirectly enabled Rho to function as a regulator of many physiological processes ( 4 ). Our laboratory has recently shown that Rho augments DNA repair ( 6 ) and controls bacterial antibiotic sensitivity via multipartite pathways ( 7 ). Likely, its RNA binding, as well as RNA translocase activities, could also impart its roles in various RNA metabolism processes, RNA chaperone activities, and RNA turnover functions.…”
Section: Discussionmentioning
confidence: 99%
“…It binds to the rut site (Rho utilization; a C-rich unstructured region) of the exiting nascent RNA, and this interaction is a prerequisite for its termination function ( 5 ). This termination function regulates many physiological processes ( 4 , 6 , 7 ), and the conserved nature of the Rho protein in a wide range of bacteria makes it an ideal target for bactericidal agents.…”
mentioning
confidence: 99%
“…Regulation of the elongation phase of transcription is important for coordination with other cellular mechanisms [60] and for preserving genome integrity [61]. Conservation of NusG and its functional homologs in all three kingdoms of life highlights the importance of this regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Images of the wounded cell monolayers were taken using a microscope (EVOS, Thermo Fisher Scientific, MA, United States) at 0 and 36 h after wounding and controlled by ImageJ software (National Institutes of Health, Bethesda, Maryland, USA). All experiments were performed in the presence of Mitomycin-C (10 μM, Selleck Chemicals, S8146) [ 37 ] to inhibit cell proliferation.…”
Section: Methodsmentioning
confidence: 99%